2002
DOI: 10.1126/science.1076521
|View full text |Cite
|
Sign up to set email alerts
|

Truncating Neurotrypsin Mutation in Autosomal Recessive Nonsyndromic Mental Retardation

Abstract: A 4-base pair deletion in the neuronal serine protease neurotrypsin gene was associated with autosomal recessive nonsyndromic mental retardation (MR). In situ hybridization experiments on human fetal brains showed that neurotrypsin was highly expressed in brain structures involved in learning and memory. Immuno-electron microscopy on adult human brain sections revealed that neurotrypsin is located in presynaptic nerve endings, particularly over the presynaptic membrane lining the synaptic cleft. These findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
161
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(170 citation statements)
references
References 26 publications
8
161
1
Order By: Relevance
“…[1][2][3] Few autosomal recessive (AR) genes and several other loci have been identified by means of linkage analysis and genome-wide homozigosity mapping in large consanguineous families followed by resenquencing of candidate genes. These include PRSS12 (MIM 606709), 4 CRBN (MIM 609262), 5 CC2D1A (MIM 610055), 6 GRIK2 (MIM 138244), 7 TUSC3 (MIM 601385), 8,9 and TRAPPC9 (MIM 611966). [10][11][12][13] The introduction of next generation sequencing techniques dramatically changed this scenario, leading to the discovery of a rapidly increasing number of AR-NSID causative genes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Few autosomal recessive (AR) genes and several other loci have been identified by means of linkage analysis and genome-wide homozigosity mapping in large consanguineous families followed by resenquencing of candidate genes. These include PRSS12 (MIM 606709), 4 CRBN (MIM 609262), 5 CC2D1A (MIM 610055), 6 GRIK2 (MIM 138244), 7 TUSC3 (MIM 601385), 8,9 and TRAPPC9 (MIM 611966). [10][11][12][13] The introduction of next generation sequencing techniques dramatically changed this scenario, leading to the discovery of a rapidly increasing number of AR-NSID causative genes.…”
Section: Introductionmentioning
confidence: 99%
“…6 Until now, 26 significantly linked non-specific intellectual disability of autosomal recessive inheritance (NS-ARID) loci were described, [7][8][9][10] and only 10 genes (six of them located in described regions) were identified: PRSS12 (OMIM#606709, on 4q26, former MRT1), CRBN (OMIM#609262, on 3p26, former MRT2), CC2D1A (OMIM#610055, on 19p13.12, former MRT3), ST3GAL3 (OMIM#606494, on 1p34.3), GRIK2 (OMIM#138277, on 6q16, former MRT6), TUSC3 (OMIM#601385, on 8p22, former MRT7), ZNF26 (no OMIM#, on 19q13.2), TRAPPC9 (OMIM#613192, on 8q24, former MRT13), ZCH14 (OMIM# 613279, on 14q31.3), and TECR (MIM*610057 on 19p13.12) (Figure 1). 1,[11][12][13][14][15][16][17][18][19] Taking into account that over 90 genes are responsible for only about 40% of X-chromosomal recessive ID cases, and that about half of the estimated 22 000 human genes are expressed in the brain, the total number of ARID genes may run into the hundreds. 1 Considering the heterogeneity observed in previous linkage studies, and the fact that the so far identified genes do not account for a significant fraction of NS-ARID cases, systematic approaches are the most promising strategy to identify further genes.…”
Section: Introductionmentioning
confidence: 99%
“…5 -7 Only two autosomal genes, the PRSS12 gene on chromosome 4q26 [MIM 606709] and the CRBN gene on chromosome 3p26 [MIM 607417], have been shown to cause autosomal recessive NSMR, each gene in only one family. 8,9 Autosomal recessive diseases are common in the Arab population of Israel, mostly as a result of the high rate of consanguinity. Among Israeli Arabs, up to 44% of the marriages used to be between relatives, approximately half of which were between first cousins, although these numbers are somewhat lower today.…”
Section: Introductionmentioning
confidence: 99%